2021
DOI: 10.1186/s12877-020-01986-x
|View full text |Cite
|
Sign up to set email alerts
|

The activity of daily living (ADL) subgroups and health impairment among Chinese elderly: a latent profile analysis

Abstract: Background Disability in aged people became one of the major challenges in China due to the acceleration of population aging. Nevertheless, there were limited methods to appropriately discriminate the degree of combined basic activity of daily living (BADL) and instrumental activity of daily living (IADL). The present study explored an empirical typology of the activity of daily living (ADL) and its association with health status among the elderly in China. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 51 publications
(53 reference statements)
2
63
1
1
Order By: Relevance
“…The measure of self-reported sleep quality was dichotomized into very good/good versus other (fair/bad/very bad), and was treated as a binary outcome. The 10-item Center for Epidemiologic Studies Short Depression Scale (CES-D) was adopted to measure the depression symptom, scoring from 0 to 30 [43,44]. ADL was based on whether the respondent could be independent in feeding, bathing, dressing, toilet hygiene, continence and indoor transferring, each item was scored from 1 to 3 (1 score representing complete independence; 2 scores representing partially dependence; 3 scores representing complete dependence), and lower scores indicating better functional independence.…”
Section: Covariatesmentioning
confidence: 99%
“…The measure of self-reported sleep quality was dichotomized into very good/good versus other (fair/bad/very bad), and was treated as a binary outcome. The 10-item Center for Epidemiologic Studies Short Depression Scale (CES-D) was adopted to measure the depression symptom, scoring from 0 to 30 [43,44]. ADL was based on whether the respondent could be independent in feeding, bathing, dressing, toilet hygiene, continence and indoor transferring, each item was scored from 1 to 3 (1 score representing complete independence; 2 scores representing partially dependence; 3 scores representing complete dependence), and lower scores indicating better functional independence.…”
Section: Covariatesmentioning
confidence: 99%
“…3 For example, previous studies showed three subgroups of disability trajectories. [8][9][10] However, Fuente et al identified four classes of health trajectories in an English Longitudinal Study of Aging sample, 11 and another study by Daskalopoulou et al reported four healthy aging trajectories, including high-stable, moderate-stable, low-stable, and decliners in a Mexican Health and Aging Study sample. 12 Also, the Taiwan Longitudinal Study on Aging (2017) regarding healthy aging identified four health profiles among the aging population.…”
Section: Introductionmentioning
confidence: 99%
“…Information on IADL disability drew on the data in the 2014 survey, including visiting neighbors, shopping, preparing meals, washing clothes, and taking public transportation. The participants were asked whether they could complete these tasks by themselves (1 = Yes, I can do it independently; 2 = Yes, but I need some help; 3 = No, I cannot do it) [ 24 ]. The total IADL disability score ranged from 5 to 15.…”
Section: Methodsmentioning
confidence: 99%